Begonia ngocbonii (sect. Petermannia, Begoniaceae), a new species from North Vietnam - Son, Hoang Thanh; Lin, Che-Wei; Bon, Trinh Ngoc (Phytotaxa, 2022)
Begonia ngocbonii, a new species from North Vietnam is here described and illustrated. It resembles B. pellionioides Y.M.Shui & W.H.Chen, but is distinguishable by its hairy (vs. glabrous) stem, shorter inflorescence up to 1 cm (vs. ca. 5 cm or longer), 2-tepaled staminate and pistillate flowers (vs. 4-tepaled staminate flowers and 5-tepaled pistillate flowers), glabrous tepals (vs. spiny pilose on abaxial surface of outer tepals) and unilamellate placenta (vs. bilamellate).